2020
DOI: 10.2147/tcrm.s265945
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of 0.01% Atropine Eye Drops on the Ocular Surface in Children for the Control of Myopia—The Primary Results from a Six-Month Prospective Study</p>

Abstract: To evaluate the effect of 0.01% atropine eye drops on the ocular surface in children for the control of myopia. Methods: A total of 72 participants were recruited for this prospective study. Prior to and after 1, 3, and 6 months of 0.01% atropine administration, an ocular surface disease index (OSDI) questionnaire was obtained, Keratograph 5M was used for the measurement of the tear meniscus height (TMH), noninvasive keratographic tear film break-up time (NK-BUT, the first keratographic break-up time, [NK-BUT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…29 However, the study of Larkin et al 30 showed that 0.01% atropine eye drops considerably slows the progression of myopia in a group of American children who have been treated for more than 2 years. In a 6-month prospective study of Cheng et al, 31 atropine at a concentration of 0.01% shows no obvious side effects on the ocular surface in children with myopia. Although studies have demonstrated the efficacy of the OK lens in the treatment of myopia, 9,10 several adverse events exist, such as keratitis, 32 the decline of tear film stability, 33 bacterial adhesion, 34 etc.…”
Section: Discussionmentioning
confidence: 92%
“…29 However, the study of Larkin et al 30 showed that 0.01% atropine eye drops considerably slows the progression of myopia in a group of American children who have been treated for more than 2 years. In a 6-month prospective study of Cheng et al, 31 atropine at a concentration of 0.01% shows no obvious side effects on the ocular surface in children with myopia. Although studies have demonstrated the efficacy of the OK lens in the treatment of myopia, 9,10 several adverse events exist, such as keratitis, 32 the decline of tear film stability, 33 bacterial adhesion, 34 etc.…”
Section: Discussionmentioning
confidence: 92%
“…Following these studies, a mass-scale use of atropine in myopia treatment in many countries has been observed. It has been found that a 0.01% solution of atropine decreases the development of myopia and does not induce side effects in the anterior segment [39][40][41][42]. It has also been observed that 0.02% atropine eye drops had a better effect on myopia progression than 0.01% atropine.…”
Section: Results Of Clinical Studiesmentioning
confidence: 97%
“…The question remains as to what precise extent continuous therapy can contribute to the risk of dry eye or a stressed surface [ 47 ]. Apart from single reports of ocular discomfort, according to the ocular surface disease index (OSDI) and the objective parameters of the tear film at break-up time, meiboscore, or the anterior segment, optical coherence tomography was not changed at all in children treated for at least six months ( n = 72) [ 60 ]. One study found no significant differences in the amount of tear secretion or signs of ocular surface inflammation between normal healthy children ( n = 38) and myopic children receiving topical atropine treatment ( n = 126) [ 61 ].…”
Section: Discussionmentioning
confidence: 99%